Launching a Successful Music Festival - Facon, Florent (My University, 2015)
This study is focused on the following topic, launching a successful new festival. The theoretical and empirical researches about the strategic and the tactical launch decision in new product development were analyzed and related to academic literatures about the festival industry and event industry. Furthermore, it also analyzes how these decisions can affect the performance of a new product launched on the market. In order to investigate the topic, a theoretical framework is used, the model of 6W’s. The framework mentioned above consists of six main points. It includes five questions: “why”, “what”, “where”, “when” and “how”. The last point is the result, which is the success. This model is adapted from previous literatures about strategic and tactical launch decision according to new product performance. The methodology used for this study is qualitative. The data collected in the empirical part is done through interviews. The interviews realized take the form of semi-structured and unstructured interviews. Since the topic is wide, it is the right choice in order to get more qualitative information. Content analysis is the method applied. Furthermore, the author has some experience about the topic, so the personal knowledge and contacts have helped. In order to launch a new successful festival the following main points have been identified. The importance of the market choice, domestic or international. The goal settings fixed, such as motivation to create a festival, the format and how the manager sees the festival. Then there are the characteristics which include concept and content. Furthermore, we can say that festival is similar to a product but it has also similarities with service, so the term productization is more appropriate. In order that the festival reach success, the target group have to be well defined and adapt to them. The launching process is crucial, and the marketing through communication and brand value have an important role.
Keywords: Festival; Launch; Decisions; NPD; Successful.; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in Strategic Management|